Low dose of chlorine exposure exacerbates nasal and pulmonary allergic inflammation in mice - de Genaro I.S. (2018)
© 2018, The Author(s).Work-exacerbated asthma (WEA) is defined as preexisting asthma that worsens with exposure to irritants [e.g., chlorine (Cl2) derivatives] in the workplace. The maximum allowable concentration in the workplace of Cl2 exposure is 3 mg/ m3 (described in OSHA). We investigated in an experimental asthma model in mice the effects of a single exposure to a sodium hypochlorite dose with this allowed chlorine concentration and a tenfold higher dose. Acute chlorine exposure at 3.3 mg/m3 in the OVA-sensitized group increased eosinophils in the peribronquial infiltrate, cytokine production, nasal mucus production and the number of iNOS positive cells in the distal lung compared to only sensitized mice. The exposure to a higher dose of 33.3 mg/m3 in the OVA-sensitized group resulted in an increase in respiratory system elastance, in the total and differential numbers of inflammatory cells in bronchoalveolar lavage fluid, IL-4, IL-5, and IL-17 in the lungs, eosinophils in peribronquial infiltrate and mucus content in nasal compared to non-exposed and sensitized animals. In this asthma model, chorine exposures at an allowable dose, contributed to the potentiation of Th2 responses. The functional alterations were associated with increased iNOS and ROCK-2 activation in the distal lung.